Condiciones de operación de un biorreactor para la fermentación en café - Peñuela Martínez, Aida Esther; Moreno Riascos, Sandra Paola; García Duque, Jhoan Felipe (Biotecnología en el Sector Agropecuario y Agroindustrial, 2023)
Fermentation at a controlled temperature is proposed as a processing alternative to obtain benefits in terms of coffee quality. The changing physical characteristics in the coffee mass during fermentation become a challenge for the stirring system to achieve homogeneous temperature conditions. A fine-tuning process was carried out to determine the operating conditions of a bioreactor for fermentation in coffee with variations in rotation speed, stirring time, and the period between stirrings. Subsequently, the behavior of the fermentations was determined in a temperature range between 10 and 30 °C, at intervals of 5 °C. As a comparison for each process, spontaneous fermentation was carried out. The time to reach mucilage degradation greater than 95 % and the time to reach equilibrium between the temperatures of the coffee mass and the equipment’s water jacket were determined. The final pH was also registered. Descriptive differences observed between the processes with controlled temperature, the spontaneous fermentation in the time to reach mucilage degradation, and the final pH and temperature values. The controlled processes required between 2 and 13 hours longer fermentations than the corresponding spontaneous process. Through a flat vane impeller, the best operating point was identified when the process was performed at 3 r•min-1 for 2 min every 6 hours. Low-speed agitation is required to reduce mechanical removal of mucilage.